2017
DOI: 10.2106/jbjs.cc.16.00151
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Bone Infarct in the Ilium Following a Pelvic Crush Injury and Embolization

Abstract: The symptoms from osteonecrosis of the ilium may simulate sacroiliitis or other conditions. It is important to keep the differential diagnosis in mind when considering additional management for posterior pelvic pain in the setting of prior trauma and preexisting hardware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Caisson disease, glucocorticoid, alcohol abuse, dyslipidemia, trauma, and chemotherapy were considered as risk factors of bone infarction. 6 In addition, bone infarction was usually found in special diseases, such as thalassemia, sickle cell disease, systemic lupus erythematosus, etc. 7 , 8 Studies had shown that the pathogenesis of bone infarction stems from local blood supply disorders in the medullary cavity or bone cortex and acute vascular obstruction (thrombosis, lipid emboli, and fat cell hypertrophy with the compression of intraosseous capillaries) leads to ischemic osteonecrosis and bone infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Caisson disease, glucocorticoid, alcohol abuse, dyslipidemia, trauma, and chemotherapy were considered as risk factors of bone infarction. 6 In addition, bone infarction was usually found in special diseases, such as thalassemia, sickle cell disease, systemic lupus erythematosus, etc. 7 , 8 Studies had shown that the pathogenesis of bone infarction stems from local blood supply disorders in the medullary cavity or bone cortex and acute vascular obstruction (thrombosis, lipid emboli, and fat cell hypertrophy with the compression of intraosseous capillaries) leads to ischemic osteonecrosis and bone infarction.…”
Section: Discussionmentioning
confidence: 99%